2020
DOI: 10.3390/v12050528
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Epidemiological Evidence of the Transmission of Avian and Human Influenza A Viruses in Wild Pigs in Campeche, Mexico

Abstract: Influenza, a zoonosis caused by various influenza A virus subtypes, affects a wide range of species, including humans. Pig cells express both sialyl-α-2,3-Gal and sialyl-α-2,6-Gal receptors, which make them susceptible to infection by avian and human viruses, respectively. To date, it is not known whether wild pigs in Mexico are affected by influenza virus subtypes, nor whether this would make them a potential risk of influenza transmission to humans. In this work, 61 hogs from two municipalities in Campeche, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(60 reference statements)
1
6
0
Order By: Relevance
“…The results of the meta-analysis showed an estimated pooled prevalence of 1.6% (95% CI: 0-5%) of IAV in pigs in Africa. This finding is comparable to a study in Cambodia which reported a prevalence of 1.5% of IAV in pigs [97] but lower than the 11.7-15.7% and 19.67% reported in Guatemala [98] and Mexico [99], respectively. Further, the meta-analysis demonstrated an estimated pooled seroprevalence of 14.9% of IAV in pigs in Africa.…”
Section: Discussionsupporting
confidence: 79%
“…The results of the meta-analysis showed an estimated pooled prevalence of 1.6% (95% CI: 0-5%) of IAV in pigs in Africa. This finding is comparable to a study in Cambodia which reported a prevalence of 1.5% of IAV in pigs [97] but lower than the 11.7-15.7% and 19.67% reported in Guatemala [98] and Mexico [99], respectively. Further, the meta-analysis demonstrated an estimated pooled seroprevalence of 14.9% of IAV in pigs in Africa.…”
Section: Discussionsupporting
confidence: 79%
“…Influenza viruses (IAVs) are enveloped viruses with a negative-sense single-stranded RNA genome that belong to the Orthomyxoviridae family, which includes the influenza A, B, C, and D genera. Influenza A is the most virulent type for humans and is a zoonotic disease that affects a large number of species [ 59 , 60 ]. Therefore, this review will focus on the influenza A virus (IAV) only.…”
Section: Influenza a Virusmentioning
confidence: 99%
“…Hong Kong [20] "Sewage rats" Presumably Rattus sp. Egypt [21] House mouse Mus musculus U.S. [4] Transbaikal hamster b Cricetulus pseudogriseus Russia [16] Campbell's dwarf hamster b Phodopus campbelli Russia [16] Brandt's vole Lasiopodomys brandtii Russia [16] Mongolian gerbil Meriones unguiculatus Russia [16] Daurian souslik Spermophilus dauricus Russia [16] Raccoon Procyon lotor U.S. [22] Japan [23,24] Arctic fox Vulpes lagopus U.S. [25] "Fox" c Not listed China [26] Black-backed jackal Canis mesomelas Namibia [17] Raccoon dog c Nyctereutes procyonoides China [26] Far-eastern wild cat Prionailurus bengalensis euptilurus Russia [27] Leopard cat Prionailurus bengalensis Korea [28] American mink Neovison vison Spain [38] Water deer Hydropotes inermis Korea [28] Feral swine Sus scrofa U.S. [30] Mexico [31] a This table is not intended to be an exhaustive list of all wild mammal exposures to influenza A viruses (IAV), as the focus of this paper is mammalian synanthropes. Some additional non-synanthropic species are listed in the text to bring attention to IAV exposures in select taxa.…”
Section: Common Name a Scientific Name Location Citationmentioning
confidence: 99%
“…In the U.S., researchers recently reported that although U.S. feral swine were predominantly exposed to swine IAVs, they may have also been exposed of avian IAVs on a less frequent basis [30]. Based on a relatively small sample size (n = 61), one feral swine in Mexico was assessed to be positive for antibodies reactive with an H5N2 virus that was presumed to be avian in origin [31]. In China, however, a small number of feral swine were reported to have been exposed to typical swine viruses (e.g., H1 and H3), but did not react to select avian viruses (e.g., H5 and H9) [48].…”
Section: Artiodactylsmentioning
confidence: 99%
See 1 more Smart Citation